Voices of the Vanguards: RTI as a Catalyst for Social Justice and Administrative Reform in Rural India - Dasari, Sairam (International Journal of Psychosocial Rehabilitation, 2019)
The Right to Information (RTI) Act of 2005 marked a watershed moment in the history of Indian democracy, fundamentally changing the culture of administration that had long been associated with colonial rule and ushering in an era of transparency and accountability. The study explores the complex effects of the Act, especially in the realization of social justice and administrative reform in rural India that has turned into a powerful tool for social justice for the weak and the disadvantaged. The Act has provided citizens with a legal right to be “vanguards” of transparency by allowing citizens to seek to uncover the government’s actions and to obtain public records, which was a culture of opacity once protected government mismanagement and corruption. The study examines how RTI has helped the rural poor demand their basic rights (ration cards, pensions, fair wages, etc.) and also make the officials accountable for their actions and inactions. The study also uncovers key implementation challenges that limit the effective potential of the Act, such as entrenched opposition among officials, neglect in record keeping and a backlog of appeals before the Information Commissions. Moreover, it covers the growing danger to the information seekers and the abuse of exemption clauses to deny information of public interest. The paper finds that fulfilling the “right to know” as a “right to live” for the rural population requires institutional reforms, better digital infrastructure and a change in the attitude of the administration authorities to cultivate a participatory and inclusive democracy.